Heidegger, philosophy, and politics : the Heidelberg Conference - Derrida, Jacques; Gadamer, Hans-Georg, 1900-2002; Lacoue-Labarthe, Philippe; Calle-Gruber, Mireille, 1945- (Fordham University Press, 2016)
"In February of 1988, Hans-Georg Gadamer, Jacques Derrida, and Philippe Lacoue-Labarthe came together in Heidelberg before a large audience to discuss, in French, the philosophical and political implications of Martin Heidegger's thought, particularly in light of the philosopher's engagement in Nazism. This book presents a transcription and translation of their reflections and exchanges with the audience"--